Pemberdayaan Masyarakat Madani Berbasis Kolaborasi Akademisi-Komunitas Lokal dalam Pengelolaan Lingkungan Berkelanjutan di Kelurahan Nginden Jangkungan Kecamatan Sukolilo Kota Surabaya - Suhartono, Slamet; Arie Mangesti, Yovita; Simangunsong, Frans; Hadi, Syofyan; Amelia, Mays; Lovitya Trisnanti, Ines; Rimbawani Sushanty, Vera; Walujo Tjahjono, Agus; Imron, Muhamad; Ronny, Ronny; Putra Samudra, Kaharudin; Guntur, Sundaru; Dahlan, Rudiyanto; Puji Utomo, Sutrisno; Aziz, Abdul; Farisi, Salman; Murtadlo, Aly; Pratama Widiarsa, Anang; Mohammad, Mohammad; Chairul Farid, Achmad; Tri Budiman, Nanang; Sibarani, Tagor (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Geographically, it is located in a strategic urban area with quite rapid development, both in terms of infrastructure development and population growth. The heterogeneous composition of its population, both in terms of education level, livelihood, and cultural background, provides both potential and challenges in efforts to create an empowered community and actively participate in sustainable environmental management. In general, most residents of Nginden Jangkungan Village work in the informal sector, such as street vendors, rental services, grocery stores, and transportation services. This is exacerbated by the community's limited technical knowledge regarding waste management based on the principles of reduce, reuse, recycle (3R), as well as the absence of an integrated and sustainable empowerment model. The implementation method of this Community Service activity is designed with a participatory and collaborative approach, prioritizing synergy between academics, the village government, community groups, and beneficiary residents. Nginden Jangkungan Village has adequate social and institutional potential to implement a civil society empowerment program in sustainable environmental management. However, this area still faces serious challenges related to the management of household liquid waste, which has not been handled optimally, so it has the potential to pollute groundwater and waterways and cause environmental health impacts.